Small and Medium Industry Development Strategy in Denpasar City for Enhancing Competitiveness in the Digital Era - I Made Adi Suwandana; Yudistira Adnyana; Putu Doddy Heka Ardana; I Made Kartika; Made Prarabda Karma; I Gede Mahatma Yogiswara Winatha (International Journal of Social Science and Business, 2026)
Small and Medium Enterprises (SMEs) play a vital role in strengthening regional economies by generating employment, increasing community income, and developing products based on local potential. However, SME development is frequently constrained by ineffective manual data management and the lack of integrated digital systems, hindering accurate monitoring and policy targeting. This study aims to analyze the current condition of SMEs in Denpasar City, evaluate the effectiveness of SME data management practices, and examine the role of stakeholders in implementing digital data collection and reporting systems to support more adaptive and competitive development strategies. Addressing an important research gap, previous studies have primarily emphasized financing and marketing, while paying limited attention to digital data integration and stakeholder collaboration at the local government level. The study adopts a mixed-methods approach, combining field observations, questionnaires, structured and in-depth interviews, and document analysis to integrate quantitative patterns with qualitative contextual insights. The research involved 100 SMEs across four sub-districts, representing variations in business scale, sector characteristics, and geographical distribution. Findings indicate that SMEs demonstrate relatively strong internal stability, reflected in the education level of business actors, social status, and labor consistency. Nevertheless, external challenges remain significant, particularly among small-scale industries and service- and retail-oriented businesses, where digital marketing adoption remains low, and market expansion is limited. Statistical results show that a substantial proportion of SMEs still rely on manual reporting and fragmented data systems, reducing policy efficiency. Therefore, this study recommends implementing an integrated digital data collection and monitoring system linked with SIINas, strengthening digital marketing capabilities, and improving production capacity to enhance SME competitiveness and support sustainable market expansion in Denpasar City.